Picturing and Preserving the War: Herbert Hahn's World War II Photograph Album - (:unkn) unknown (My University, 2018)
Following his return from World War II, Herbert Hahn assembled an album using photographs he had taken during the war, photographs he had collected, and other materials that he had acquired during his time overseas. This thesis addresses questions posed by the album in Hahn’s collection, including: What was the purpose of the photographs taken by Hahn? Why did he assemble them into an album, which he then kept hidden? And, finally, what can the photograph album contribute—beyond understanding Hahn’s experiences—to larger discussions regarding soldiers’ personal photograph collections. While there is no single answer as to why Hahn created the photograph album, the album appears to have been a vehicle used by Hahn to grapple with his experiences in World War II and the resulting stress and trauma. Although incomplete, the album presents a historical record of Hahn’s experiences during World War II that shed light on broader issues of provenance, soldier photography, and the processing of trauma.
Keywords: Photograph Album; Photograph Collections; Soldier Photography; World War II